La gouvernance : étude d’un échantillon de 22 entreprises en Guyane française - Paul Roselé Chim (Études Caribéennes)
Governance plays an essential role in the operation and improvement of the performance of companies by properly defining their structuring to adapt to changes in the economic environment. To think that all societies could apply identical rules of governance would be disturbing, even destabilizing for a system which is otherwise generally good at always seeking greater coherence and efficiency. In discussions on governance and performance, the manager occupies a major place in the process leading to the creation of wealth. This paper focuses on studying corporate governance through a sample of 22 companies of fairly varied sizes which covers the entire economy of French Guiana.